Cannibalism, Cultural Identity, and the Discursive Construction of the “Savage” in Western Frontier Narratives - Dr. Abdelkader MAKHLOUF; Dr. Amel MAY (Journal of the West, 2026)
Cannibalism has been a concept that has held a significant position in the historical imagination of Western societies. From initial European interactions with the Americas to tales of the American frontier in the nineteenth century, the idea of cannibals has acted as a symbolic representation of extreme cultural difference. Rather than merely being a reference to extreme human practices, cannibalism has often been a discursive device through which Western societies have created a moral order between civilization and savagery. In this article, the function of cannibal discourse within Western historical narratives is analyzed from a Critical Discourse Analytical approach. The theoretical contributions of Norman Fairclough and Teun A. van Dijk are utilized to examine the function of linguistic representations of cannibalism as a device for creating ideological constructions of cultural identity within a historical period of colonial expansion. Special attention is devoted to the historical narrative of the Donner Party tragedy of 1846–1847, which turned out to be one of the most popular cases of survival cannibalism in the American West. The article utilizes various methods of historical study and discourse analysis to examine the symbolic significance of cannibalism, which acts as boundary markers of Western culture and identity, and to examine the legitimization of ideologies of the American West. This study seeks to develop interdisciplinary research in the fields of history, discourse studies, and culture.